(untitled) (KONFERENSIYA, 2025)
Teaching English as a Second Language (ESL) remains a complex pedagogical process influenced by linguistic, cultural, psychological, and technological factors. This article examines the major challenges faced by ESL teachers, including learners’ limited exposure, differences in learning styles, shortage of qualified teachers, insufficient teaching materials, and assessment difficulties. The study analyzes methodological strategies used to overcome these barriers and highlights the results of practical observations conducted in multilingual classrooms. Findings suggest that successful ESL instruction requires a combination of learner-centered approaches, technology integration, and continuous teacher training.